A global–local approach to predict the fretting-fatigue failure of clamped aluminum powerline conductors: From mono-contact crossed wires to full conductor vibrational tests. (April 2023) - Said, Julien; Fouvry, Siegfried; Cailletaud, Georges; Basseville, Stéphanie; Coulangeon, Marc; Brocard, Jérôme; Yang, Christine; Hafid, Fikri
Highlights: Investigation of the fretting fatigue endurance of 1XXX aluminum crossed wire contact. Calibration of the optimal critical distance method using a reference fretting fatigue endurance condition. The SWT criterion gave the best lifetime estimates as well as the shorter critical distance. Experiments and simulations of a real multi-strand cable structure subjected to vibrational loadings. Processing analysis of cable failures confirm the SWT calibrated critical distance methodology. Abstract: This work focuses on a multiscale analysis of the fretting-fatigue endurance of aluminum strands within overhead conductors. Based on experimental results, Crossland, Fatemi Socie and SWT fatigue criteria were applied using a Finite Element Method (FEM) modeling. These were used with the critical distance method calibrated on the fretting-fatigue failure of crossed mono-contact strands. With this strategy, the SWT criterion gave the best lifetime estimates as well as the shorter critical distance. By conducting a stress gradient analysis, it is concluded that the shorter the critical distance, the better the contact stress description and finally the better the prediction. This optimized critical distance – stress gradient strategy is then transposed to the complete 3D simulation of a complete multi-strand cable structure subjected to vibrational bending loadings. The comparison with real structural tests confirms the capacity of the proposal to estimate the fretting-fatigue risk.